Cantharidin and sodium fluoride attenuate the negative inotropic effect of the A1-adenosine receptor agonist N6-(R)-phenylisopropyl adenosine in isolated human atria - R. Schwarz; B. Hofmann; U. Gergs; J. Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Cantharidin and sodium fluoride inhibit the activity of serine/threonine protein phosphatases 1 (PP1) and 2A (PP2A) and increase the force of contraction in human atrial preparations. R-phenylisopropyl adenosine (R-PIA) acts as an agonist at A 1 -adenosine receptors. R-PIA exerts a negative inotropic effect on human atria. The effect of R-PIA—and its various manifestations—are currently explained as a function of the inhibition of sarcolemmal adenylyl cyclase activity and/or opening of sarcolemmal potassium channels. We hypothesise that cantharidin and sodium fluoride may attenuate the negative inotropic effect of R-PIA. During open heart surgery, trabeculae carneae from the right atrium were obtained for human atrial preparations (HAPs). These trabeculae were mounted in organ baths and electrically stimulated at 1 Hz. Furthermore, we studied isolated electrically stimulated left atrial (LA) preparations from female wild-type mice (CD1). The force of contraction was recorded under isometric conditions. R-PIA (1 µM) exerted a rapid negative inotropic effect in the HAPs and mice LA preparations. These negative inotropic effects of R-PIA were attenuated by pre-incubation for 30 min with 100-µM cantharidin in HAPs, but not in mice LA preparations. Adenosine signals via A 1 receptors in a species-specific pathway in mammalian atria. We postulate that R-PIA, at least in part, exerts a negative inotropic effect via activation of serine/threonine phosphatases in the human atrium.